ANALISIS EFISIENSI PRODUKSI PERTANIAN SAYURAN DI KABUPATEN KAMPAR ANALYSIS OF PRODUCTION EFFICIENCY OF VEGETABLE FARMING IN KAMPAR REGENCY - Dede Wiranda; Syaiful Hadi; Djaimi Bakce (Indonesian Journal of Agricultural Economics, 2018)
Kampar Regency is the district with the largest harvest area of vegetable production in RiauProvince. Nevertheless, vegetable production and productivity in Kampar District are fluctuatingwith a downward trend. Inappropriate vegetable cultivation technique in Kampar regency is oneof the factors causing fluctuation of production and it is suspected that vegetable farming is notefficient. The aim of this research was to know production efficiency of vegetable farming inKampar Regency. The analysis method used was descriptive analysis method and DEA (DataEnvelopment Analysis) method. The sample consisted of 31 spinach farmers, 31 water spinachfarmers, 30 cucumber farmers, 42 chili farmers, and 40 peanut farmers. The results of this studyindicated that the vegetable cultivation technique in Kampar Regency has not been conducted inaccordance with the recommendations. The result of production efficiency using DEA showedthat proportion of technically inefficient farmers were quite high. Technical inefficiency wascaused by input expenditure. Proportion of efficient farmers by allocation and economy wererelatively small. Allocative inefficiency was more caused by the combination of incorrect input.Economical inefficiency was mostly caused by farmers who were not efficient by allocation.